An analysis about the hidden transcript of the Emperor Marcus Aurelius Carinus (282-285 AD) - Silva, Diogo Pereira da (Romanitas - Revista de Estudos Grecolatinos, 2014)
In this article, we aim to analyze the representation of the Roman Emperor Marcus Aurelius Carinus (282-285) from the theoretical framework of the public transcript, as proposed by James C. Scott in his book Domination and the arts of resistance: hidden transcripts. The analysis of the public transcript of Carinus allows us to discuss the factors that characterized the Roman imperial power during the Third Century AD, as for instance the importance given to family relationships and the deities’ support as factors of legitimacy of the political power.